2005
DOI: 10.1007/s10549-005-3782-1
|View full text |Cite
|
Sign up to set email alerts
|

The Pilot Trial on Intraoperative Radiotherapy with Electrons (ELIOT): Update on the Results

Abstract: The first group of patients treated with ELIOT in the phase I-II trial are confirming the good impact of the procedure in terms of tolerance and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 16 publications
(15 reference statements)
1
33
0
3
Order By: Relevance
“…More recently, IORT with electrons has been used as the sole form of radiation treatment for patients with early breast cancer. Several studies on this topic have been published by the group of the European Institute of Oncology in Milan, Italy [11,18,32,33]. In the first pilot study, Veronesi et al reported that a single fraction of 21 Gy prescribed at the 90% isodose (23.3 Gy at Dmax) can be safely applied intraoperatively and is biologically equivalent to a 60-Gy dose delivered by EBRT in 30 fractions [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, IORT with electrons has been used as the sole form of radiation treatment for patients with early breast cancer. Several studies on this topic have been published by the group of the European Institute of Oncology in Milan, Italy [11,18,32,33]. In the first pilot study, Veronesi et al reported that a single fraction of 21 Gy prescribed at the 90% isodose (23.3 Gy at Dmax) can be safely applied intraoperatively and is biologically equivalent to a 60-Gy dose delivered by EBRT in 30 fractions [32].…”
Section: Discussionmentioning
confidence: 99%
“…In the first pilot study, Veronesi et al reported that a single fraction of 21 Gy prescribed at the 90% isodose (23.3 Gy at Dmax) can be safely applied intraoperatively and is biologically equivalent to a 60-Gy dose delivered by EBRT in 30 fractions [32]. The last published study analyzed 590 patients treated by a single 21-Gy dose after breast-conserving surgery [18]. After a median follow-up of 24 months, three patients developed a local relapse, three patients ipsilateral carcinoma in another quadrant of the breast, five patients contralateral breast cancer, and 13 patients distant metastases without local relapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cirurgia conservadora de mama, a biópsia do linfonodo sentinela e a radioterapia intra-operatória associada à cirurgia conservadora 33 são avanços que podem contribuir para uma melhor percepção da QV. Intuitivamente, acredita-se que essas abordagens relacionem-se à melhor QV.…”
Section: Cirurgiaunclassified
“…Dabei erhielten 10 Patientinnen eine einmalige Dosis von 10 Gy und 7 Patientinnen von 15 Gy, der anschließend eine perkutane Brustbestrahlung mit in der Regel 50 Gy in jeweils 2 Gy-Fraktionen folgte. Die restlichen 84 Fälle wurden alleinig intraoperativ mit Dosen von 17, 19 oder 21 Gy bestrahlt [13].…”
Section: Introductionunclassified